STUDI KASUS DI LPKA KELAS II TOMOHON PADA REMAJA YANG MELAKUKAN PENIKAMAN - Rinna Yuanita Kasenda; Gustina Pandiangan; Galuh Aransiti Khan; Revalina Korompot (LPPM Universitas Cipta Mandiri, 2024)
This research aims to determine the trauma experienced by one of the teenagers at LPAK Class II Tomohon. This research uses a qualitative method with a case study approach. Data collection was carried out by interviews, observation and documentation. The number of research participants was 1 person, namely a high school teenager. In socializing, participants simply interact with people who are not the same age. This research aims to determine the trauma experienced by participants.